Shaping the Future of Music with Augmented Reality: A Systematic Literature Review on Future Trends and Innovations - Mohamad Rasli, Ruziana; Rasalingam, Rasslenda-Rass; Mohamad Rasli, Roznim (Wacana Seni Journal of Arts Discourse, 2026)
This study addressed the problem of the increasing number of articles on augmented reality and aimed to isolate only those algorithms and applications dealing with the music sector. A systematic literature review model was employed. This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model, widely recognised for its comprehensive and standardised approach to conducting systematic reviews. The PRISMA model was chosen due to its emphasis on transparency, replicability, and thorough documentation of each step in the review process. The systematic search strategy involved querying multiple academic databases, targeting journal and conference articles published since 2015 that either directly involve the music sector or engage in inter-sectoral collaborations. Inclusion and exclusion criteria were meticulously defined, ensuring that only relevant studies were considered, with a focus on those that contributed significantly to the field of music augmented reality. Data synthesis was carried out by categorising and analysing the identified studies based on their methodologies, applications, and outcomes. One of the most significant findings is the relatively slow development of augmented reality in the music sector despite the overall growth in augmented reality research. This study highlights the potential of advanced augmented reality techniques to revolutionise music presentation and interaction, fostering new ways for musicians to engage with audiences.